The specificity of training : new insights from molecular biology / Vernon G. Coffey and John A. Hawley - G. Coffey, Vernon; A. Hawley, John (Faculty of Sports Science and Recreation, 2005)
The key overload components of a training programme are volume, intensity and frequency, with the specific adaptive process occurring with exercise dependent on the training stimulus. Periodised training of sufficient overload initiates a cascade of events in muscle that results in modification of adaptive responses. Chronic adaptations are likely the result of the cumulative effects of repeated bouts of exercise with the initial cellular responses that lead to these long-term adaptations occurring after each training session. The training specific adaptive response is influenced by numerous factors including the overload stimulus and individual muscle fibre type. Comparing the distinct adaptive responses in skeletal muscle to endurance versus heavy resistance training highlights this process. This brief review summarises some of the specific adaptations associated with heavy resistance training, endurance training, and concurrent training.